An intertemporal asset pricing model with stochastic consumption and investment opportunities - Breeden, Douglas T. (Journal of Financial Economics, 1979)
This paper derives a single-beta asset pricing model in a multi-good, continuous-time model with uncertain consumption-goods prices and uncertain investment opportunities. When no riskless asset exists, a zero-beta pricing model is derived. Asset betas are measured relative to changes in the aggregate real consumption rate, rather than relative to the market. In a single-good model, an individual's asset portfolio results in an optimal consumption rate that has the maximum possible correlation with changes in aggregate consumption. If the capital markets are unconstrained Pareto-optimal, then changes in all individuals' optimal consumption rates are shown to be perfectly correlated.